Secondary ejaculatory duct obstruction: Management by secondary transurethral resection of ejaculatory duct - Orhan, I; Onur, R; Ardicoglu, A; Semerciöz, A; Köksal, IT (Taylor & Francis Inc, 2005)
Distal ejaculatory duct obstruction (EDO) is a relatively rare but surgically treatable cause of male infertility. Transrectal ultrasonography (TRUS) has been commonly used in infertility evaluation in recent years. These pathologies are more common than expected and treated with transurethral resection of ejaculatory duct (TURED). Although TURED is the recommended routine procedure for all cases of EDO, it has complications, such as iatrogenic obstruction, in 4% of the cases. Herein, we evaluated a patient who had developed EDO secondary to TURED.
Keywords: ejaculatory ducts; infertility; male; obstruction